SYSTEMATIC LITERATURE REVIEW: ANALISIS PENGARUH SELF-CONFIDENCE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Annisa Nur Satifa; Nindiasari, Hepsi; Yuhana, Yuyu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of self-confidence mathematical problem-solving abilities as well as the relationship between these two variables. The method used is a Systematic Literature Review (SLR) referring to the PRISMA stages, which include the formulation of research questions, literature identification, screening process, followed by eligibility and inclusion. From a total of 20 accredited and reputable articles ranging from SINTA 4 to SINTA 2 and Scopus-indexed journals published between 2018 and 2025, 16 articles met the inclusion criteria and were analyzed using a descriptive qualitative approach with student subjects including elementary, junior high, and senior high school levels. The inclusion criteria used were: (1) articles discussing self-confidence and mathematical problem-solving ability, (2) empirical research articles, and (3) articles published within a relevant time frame (a maximum of the last 10 years). The results show that self-confidence has a positive effect on mathematical problem-solving ability with varying levels of contribution, and also has a significant relationship with that ability. In addition, the findings indicate that self-confidence plays a role in supporting students' thinking processes in solving mathematical problems. Thus, it can be concluded that self-confidence is an important factor in improving students' mathematical problem-solving abilities, although its influence is contextual and affected by other factors.